Commercialisation fears and preferred forms of governance: a mixed methods investigation to identify a trusted Australian genomics repository - Elphinstone, Brad; Walshe, Jarrod; Nicol, Dianne; Taylor, Mark (Frontiers in Public Health, 2024)
This study aimed to identify operating conditions and governance mechanisms that would help to facilitate trust in, and willingness to donate to, a hypothetical Australian national genomic repository for health research where commercial use of data is permitted. Semi-structured telephone interviews with members of the Australian public (N = 39) clarified perceived risks and preferred repository conditions. These insights were subsequently tested experimentally in a national sample (N = 1,117). Contrary to what was expected based on the interviews, when certain baseline operating conditions were included (e.g., public management, data access committee to ensure data is restricted to human health research), none of the additional tested governance mechanisms (e.g., financial penalties for misuse) increased trust or donation willingness. Thus, providing suitable baseline conditions are in place, a feasible Australian genomic repository may not require external oversight or new legislation to optimize recruitment, even if commercial users are anticipated.